Tertiary music students' appreciation of Western classical music and the repertoire of their instrumental study - Soo, Choy Wah; Chan, Cheong Jan (Faculty of Music and Performing Arts, Universiti Pendidikan Sultan Idris, 2014)
This study intends to determine the extent to which tertiary music students appreciate Western classical music and the instrumental repertoire that they are studying. Specifically it intends to determine the knowledge students have towards Western classical music and the repertoire of their instrumental study, e.g. composer, composers’ works, composer’s social background, composer’s purpose, and to determine students’ values towards classical music and the repertoire of their instrumental study as to how much they value the music and why. A listening test is conducted with selected 24 excerpts of major classical work from Baroque to early 20th century period. From the finding of the study, only 17.5% of the respondents achieved Moderate and Ideal level of appreciation towards Western classical music. 73.9% of the respondents preferred the classical music that they listened to, but only 38.5% thought that the music is valuable.